THE EFFECTIVENESS OF THE IMPLEMENTATION OF THE INTEGRATED ODGJ FAST HANDLING SYSTEM PROGRAM (SICEPOT) AT THE TIPAR HEALTH CENTER, SUKABUMI CITY - Angga Kurnia Yudha Perdana; Tuah Nur; Dine Meigawati (DIA: Jurnal Administrasi Publik, 2024)
The Integrated Rapid Treatment System for ODGJ (SICEPOT) is a program created by the Tipar Health Center with the aim of reducing the number of ODGJ in the UPTD area of the Tipar Health Center. This study aims to provide easy health services to increase awareness, families of people with ODGJ and care for their family members regularly so they can live more independently. This study aims to find out how the effectiveness of the SICEPOT program is. In measuring this effectiveness, this research uses Duncan's theory (in Streers, 2020: 53). There are 3 criteria that are measured in Effectiveness according to Duncan (in Streers 2020: 53), namely: 1. Goal Achievement, 2. Integrity, 3. Adaptation. The research method used in this research is qualitative. The results of this study have not been said to be effective because the Tipar Health Center in practice still does not meet the 3-dimensional criteria